دراسة تحليلية لمنهج تدريس المفردات العربية في كتاب تعليم اللغة العربية للصف السادس الابتدائي لوزارة الشؤون الدينية الإندونيسية عام 2020 - Ainun Suci Qurani; Sri Rezeki; Sadiyah Ratnasari Sagala; Husnul Khatimah (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2022)
The purpose of this research was to find out the method of teaching vocabulary and the knowledge of analysis methodology in teaching vocabulary of Arabic book at the 6th elementary school student of the ministry of religion RI 2020. The kind of this research was descriptive analysis method; analysis that focused on the sufficient and accurate phenomena, the known periods time, And the analysis. The result of this research 1) teaching of vocabulary by using the picture commonly was appropriate. 2) teaching of vocabulary by using the sound was applied for al-istima' and al-kalam,, 3) teaching of vocabulary by using the text was exact with the theme, 4) teaching by using the dialogue helped the students to improve their speaking skill, 5) teaching by using at-tarakiib was exact with the intellectual content of students, 6) teaching of vocabulary by using at-tadribaat helped students to inprove their understanding abaut the meanin. 7) the table of vocabulary and its translation can inprove students comprehension abaut the meaning of vocabulary.